TESTING OF BRUSHLESS DC MOTORS ENGINEERED FOR LIGHTWEIGHT AERIAL PLATFORMS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
Low-power motors and drives are becoming increasingly common, especially in large-scale products such as household electronics, toys, and laboratory equipment. Having a flexible in-house production line appears to be a significant priority for many European countries. This paper outlines a recommended procedure for developing such drives and presents a real-world development application: a 400W Brushless DC (BLDC) motor prototype, including preliminary and endurance tests. The prototype was tested as a free-running motor, a generator, and a full-power motor, and the tests confirmed that the performance goals were met.
Keywords: Brushless DC motor; Prototype development; Evaluation test